2018
DOI: 10.1111/ecc.12946
|View full text |Cite
|
Sign up to set email alerts
|

Improving the delivery of physical activity services in lung cancer: A qualitative representation of the patient’s perspective

Abstract: Objective To explore patient experiences of, and preferences for, physical activity after a lung cancer diagnosis. Methods This was a qualitative study involving seven patients who had been treated for lung cancer within the previous 2 years. Participants attended a focus group interview. Conventional content analysis methodology was used to analyse the text by two independent researchers. Results Eight major themes emerged from the data. These were as follows: the influence of past lifestyle and chronic disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…Results from this narrative analysis expand on existing literature examining patients with advanced lung cancer [30,[50][51][52]. This study focused on daily physical activities, which were modified by participants themselves according to their physical, psychological, social, and spiritual capabilities, and revealed that patients reported diverse ranges of exercise.…”
Section: Methodsological Considerationsmentioning
confidence: 72%
See 1 more Smart Citation
“…Results from this narrative analysis expand on existing literature examining patients with advanced lung cancer [30,[50][51][52]. This study focused on daily physical activities, which were modified by participants themselves according to their physical, psychological, social, and spiritual capabilities, and revealed that patients reported diverse ranges of exercise.…”
Section: Methodsological Considerationsmentioning
confidence: 72%
“…In our study, participants believed that their expectations of exercise were not only achievable [52], but also boosted themselves to be healthy cancer survivors. For those who had no previous exercise behaviors, they also accepted suggestions from other people and began exercising either after diagnosis or after starting treatment [50]. As caused by physical capacity that declined relative to their past conditions, one should recognize that symptoms such as breathlessness, weakness, and fatigue, were usually taken as early warning signals of the disease [29].…”
Section: Primary Findingsmentioning
confidence: 99%
“…These symptoms can significantly affect their capacity to perform ADLs as well as physical activity. 19,20 One-third of people with lung cancer attribute major impairments in their ADLs to their diagnosis, and patient-reported symptoms have changed little over a 10-year period. 21 The most commonly reported symptoms in those with newly diagnosed lung cancer include pain, fatigue, loss of appetite, coughing and sleep disturbance.…”
Section: Symptoms Of Lung Cancer and Their Impact On Physical Activitymentioning
confidence: 99%
“…Symptom management has important implications for improving other outcomes in this population, including physical function and HRQoL, where uncontrolled symptoms may contribute to people reducing their physical activity levels or avoiding certain activities for fear of exacerbating symptoms. 20 Routine symptom self-reporting, with severe symptom ratings or significant increases triggering email alerts to hospital nurses, was found to result in reduced emergency department and hospital admissions, and improvements in chemotherapy tolerance, HRQoL and survival for patients with several types of metastatic cancer. 24 Similar approaches to post-discharge symptom monitoring have been embedded into electronic health records in the UK for patients with cancer following surgery.…”
Section: Symptoms Of Lung Cancer and Their Impact On Physical Activitymentioning
confidence: 99%
“…In the future we need data to inform the optimal timing for exercise training commencement. However, an immediate challenge for patients is access to exercise programs (10,37). This is because oncology exercise programs are not readily available throughout many countries in the world, and therefore encouraging patients to access programs when and where available should be a priority until these data are available to change our practice.…”
mentioning
confidence: 99%